2002
DOI: 10.1002/etc.5620211019
|View full text |Cite
|
Sign up to set email alerts
|

Level and extent of mercury contamination in Oregon, USA, lotic fish

Abstract: We conducted a probability survey of 154 Oregon, USA, stream and river sites to assess the spatial extent of mercury (Hg) contamination in fish tissue. Samples consisted of whole-fish analyses of both small (<120 mm) and large (>120 mm) fish at each site, when both were present. Overall, Hg levels (microgram/g) in small fish (mean = 0.031; standard deviation [SD] = 0.029), large piscivores (mean = 0.284; SD = 0.175), and large invertivores (mean = 0.055; SD = 0.047) were found within fairly narrow ranges; alwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…Future studies would require a moisture determination for each sample or would have to rely on moisture values from other studies. Alternatively, the samples could be analyzed wet by CA-AAS (e.g., Peterson et al 2005), but precision is generally lower due to among-sample moisture differences and the samples would have to be analyzed soon after collection to avoid moisture loss; Peterson et al (2002) Blood Hg, µg/mL demonstrated that plug samples can be stored for up to 100 days. Negative attributes of the biopsy punch include the generation of solid waste and the relatively large, visible wound it leaves, which would presumably be sealed prior to releasing the fish (Baker et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies would require a moisture determination for each sample or would have to rely on moisture values from other studies. Alternatively, the samples could be analyzed wet by CA-AAS (e.g., Peterson et al 2005), but precision is generally lower due to among-sample moisture differences and the samples would have to be analyzed soon after collection to avoid moisture loss; Peterson et al (2002) Blood Hg, µg/mL demonstrated that plug samples can be stored for up to 100 days. Negative attributes of the biopsy punch include the generation of solid waste and the relatively large, visible wound it leaves, which would presumably be sealed prior to releasing the fish (Baker et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is also not appropriate for threatened or endangered species. Studies conducted elsewhere have demonstrated the utility of muscle biopsy sampling as an alternative to sampling fillets or whole fish for Hg monitoring (Baker et al 2004;Cizdziel et al 2002aCizdziel et al , 2003Peterson et al 2002Peterson et al , 2005Uthe 1971) and selenium (Hamilton et al 2004;Waddell and May 1995) and for obtaining samples for genetic analyses (Crawford et al 1977;Leitner and Isely 1994). The analysis of scales (Lake et al 2006) and caudal fin tissue (Gremillion et al 2005) have also been evaluated for Hg.…”
mentioning
confidence: 99%
“…The Beckvar et al [8] TRV of 0.2 mg/kg falls at the high end of present-day background concentrations of mercury in larger fish ( Table 5), but fish tissue mercury concentrations [129] comparable to this TRV apparently can occur naturally under conditions that favor mercury methylation, such as in dystrophic lakes or in watersheds with abundant forest and wetland cover [32,35,102]. Taken together with the uncertainties in the data underlying this TRV (see section Review of fish tissue TRVs), it would appear that the Beckvar et al [8] TRV is lower than necessary for protection of adult and early life stages of fish.…”
Section: Background Concentrationsmentioning
confidence: 93%
“…Historical disturbances in the 19th century (overfishing, hatcheries, logging, channelization, estuary restructuring, and fire) have influenced the biological integrity of streams, but often are not evident in current habitat and land use descriptors (Benner and Sedell 1997;Harding et al 1998;Connolly and Hall 1999). Reduced numbers of returning adult salmon and the resultant lower nutrient inputs (Gresh et al 2000) are not detected by our human disturbance measures, nor are chronic levels of atmospheric contaminants like mercury (Peterson et al 2002). All of these factors may mean that our reference sites were degraded somewhat from historical or natural conditions.…”
Section: Relationship Of Ibi To Anthropogenic Disturbancesmentioning
confidence: 97%